Revolution oder Evolution der Historsichen Geographie? - Jäger, Helmut (ERDKUNDE, 1982)
Geographical research into fundamentals includes all spheres of enquiry, methods and processes which address themselves to the synchronic and diachronic investigations of the formal, functional and dynamic spatial structure of the past. This requires a firm establishment, though not a persistence, in empirical material as a basis. Some problems can only be solved in co-operation with the geography of nature. Historical-geographical atlases and 'historical geographies' are the two most important forms of synoptic presentation. Horizontal and vertical approaches are the fundamental forms of perception, without which historical-geographical concepts and work are not possible. Being mere forms of cognition they do not state anything about objects, but are thus perfectly open to traditional, as well as new, interpretations of the geographical province of existence.